2014
DOI: 10.1039/c4ra11300d
|View full text |Cite
|
Sign up to set email alerts
|

Fractality and metastability of a complex amide cross-linked dipodal alkyl/siloxane hybrid

Abstract: A novel room-temperature white light emitter amide-cross linked alkyl/siloxane hybrid material (amidosil A) was produced by selforganization through the rational design of the precursor. This hybrid displays a highly complex hierarchical architecture composed of two lamellar bilayer structures, the relative spatial arrangement of which yields a multiplicity of ordered nanodomains with variable shapes and sizes, some of them persisting at the microscale. Macroscopically A was obtained as clusters of hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…These unprecedented findings unequivocally demonstrated that we succeeded in producing a non‐bridged silsesquioxane material in which the time scale of the morphogenesis was such that it became possible to capture two different types of shapes and morphologies, associated with two distinct stages of the process: hemispheres, which represented an advanced phase of self‐similar branching (fractal growth), and closed spherocrystals, which corresponded to its completion …”
Section: Synthesis Of Organized Hybridsmentioning
confidence: 73%
See 2 more Smart Citations
“…These unprecedented findings unequivocally demonstrated that we succeeded in producing a non‐bridged silsesquioxane material in which the time scale of the morphogenesis was such that it became possible to capture two different types of shapes and morphologies, associated with two distinct stages of the process: hemispheres, which represented an advanced phase of self‐similar branching (fractal growth), and closed spherocrystals, which corresponded to its completion …”
Section: Synthesis Of Organized Hybridsmentioning
confidence: 73%
“…The design of the new precursor 4 included a secondary amide group and a tertiary amide group both linked to pendant alkyl chains with 13 carbon atoms (Figure ). This modification gave rise to two lamellar bilayer structures, which resulted in a series of unique nanoregions, some of which manifested at the microscale . Macroscopically the hybrid system was obtained as clusters of hydrophobic hemispherical and spherical micro‐objects exhibiting a lettuce coral‐like pattern (Figure A).…”
Section: Synthesis Of Organized Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…BSs incorporating hydrophobic alkyl chains and suitable cross-links composed of hydrogen donor and acceptor groups able to establish hydrogen bonding interactions (e.g., a urea or an amide groups) have been extensively explored (Moreau et al, 2001 ; Besson et al, 2010 ; Fernandes et al, 2011b ; Nunes et al, 2015b ). A convenient and widely used strategy to promote structuring in NBSs is the use of non-bridged organosilanes carrying exclusively pendant alkyl chains (Parikh et al, 1997 ; Shimojima et al, 1997 ) or alternatively alkyl chains and suitable cross-links (Carlos et al, 2007 ; Nunes et al, 2012 , 2013 , 2014a , b , 2015a ; Fernandes et al, 2013 ). A completely different approach was introduced by Besnard et al ( 2013 , 2016 ) to tune the structure of aminoundecyltriethoxysilane-derived silsesquioxanes in acidified water.…”
Section: Introductionmentioning
confidence: 99%
“…[1]. Materials from the natural world are known to be complex systems which provide plenty of inspiring examples of hierarchical arrangement, self‐similarity growth and emergent phenomena. In the last few years biomimetic strategies have been extensively adopted by the community of materials science with the goal of designing innovative materials exhibiting the extraordinary features offered by materials in Nature.…”
Section: Introductionmentioning
confidence: 99%